Genome-Wide Identification and Comparative Analysis of the Teosinte Branched 1/Cycloidea/Proliferating Cell Factors 1/2 Transcription Factors Related to Anti-cancer Drug Camptothecin Biosynthesis in Ophiorrhiza pumila - Wang, Can; Hao, Xiaolong; Wang, Yao; Shi, Min; Zhou, Zhi-Gang; Kai, Guoyin (Frontiers in Plant Science, 2021)
Ophiorrhiza pumila is a medicinal herbaceous plant which can accumulate camptothecin (CPT). CPT and its derivatives are widely used as chemotherapeutic drugs for treating malignant tumors. Its biosynthesis pathway has been attracted significant attention. Teosinte branched 1/cycloidea/proliferating cell factors 1/2 (TCP) transcription factors (TFs) regulates a variety of physiological processes, while TCP TFs in regulation of CPT biosynthesis remains unclear. In this study, a systematic analysis of the TCP TFs family in O. pumila was performed. A total of 16 OpTCP genes were identified and categorized into 2 subgroups based on their phylogenetic relationships with those in Arabidopsis. Tissue-specific expression patterns revealed that nine OpTCP genes have the highest expression levels in leaves, while the other seven OpTCPs showed a higher expression level in the stems. Combining the results of co-expression and phylogeny analysis revealed that OpTCP5 and OpTCP15 potentially play important roles in CPT biosynthesis. In addition, subcellular localization experiment of candidate OpTCP genes showed that they are all localized in the nucleus. Our study lays a foundation for further functional characterization of the candidate OpTCP genes involved in CPT biosynthesis regulation, and provides new strategies for increasing CPT production.